The Impact of Green Accounting, Independent Commissioners, Environmental Performance, and Firm Size on Financial Performance: Evidence from Indonesia’s Energy and Basic Materials Sector - Dwi Hidayatul Khamaliya; Rezza Arlinda Sarwendhi; Agustina Ratna Dwiati; Diyah Pujiati; Dewi Murdiawati (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This study aims to determine the effect of green accounting, an independent board of commissioners, environmental performance, and company size on financial performance. This research employs quantitative methods and utilizes secondary data obtained from the annual reports and sustainability reports of raw materials and energy companies listed on the Indonesia Stock Exchange for the 2021-2024 period. The sample was selected using a purposive sampling method, resulting in 82 samples. Th The novelty in the research is the calculation of green accounting which involves the environmental costs incurred by the company in maintaining the ecosystem and its relation to profit. The results indicate that green accounting and an independent board of commissioners have no effect on financial performance. Meanwhile, environmental performance and company size do influence financial performance. Green accounting, an independent board of commissioners, environmental performance, and company size simultaneously influence financial performance. This research is expected to improve companies' long-term financial performance, attract investors concerned with environmental and social issues, and enhance their reputation among stakeholders. With this research, it is expected to contribute ideas and enrich the literature in the field of corporate finance in research on the influence of green accounting, corporate governance, environmental performance, and company size. In addition, this study is also expected to serve as a reference for future research, so that it can be further developed and refined to enrich the literature in the fields of accounting, finance, and corporate sustainability.